2013
DOI: 10.1021/jm401312n
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Translation Inhibitors Targeting the Internal Ribosomal Entry Site

Abstract: The internal ribosome entry site (IRES) in the 5′ untranslated region (UTR) of the hepatitis C virus (HCV) genome initiates translation of the viral polyprotein precursor. The unique structure and high sequence conservation of the 5′ UTR render the IRES RNA a potential target for the development of selective viral translation inhibitors. Here, we provide an overview of approaches to block HCV IRES function by nucleic acid, peptide and small molecule ligands. Emphasis will be given to the IRES subdomain IIa whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 127 publications
2
92
0
1
Order By: Relevance
“…Internal loops and bulges that occur within the Hepatitis C IRES have been extensively studied as known drug target sites (Kikuchi et al 2005;Davis and Seth 2011;Dibrov et al 2014). In vitro studies and crystal structures demonstrate that small molecules such as benzimidazole bind to the loop motifs within the HCV IRES, induce a conformational change, and effectively inhibit viral translation (Paulsen et al 2010;Dibrov et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Internal loops and bulges that occur within the Hepatitis C IRES have been extensively studied as known drug target sites (Kikuchi et al 2005;Davis and Seth 2011;Dibrov et al 2014). In vitro studies and crystal structures demonstrate that small molecules such as benzimidazole bind to the loop motifs within the HCV IRES, induce a conformational change, and effectively inhibit viral translation (Paulsen et al 2010;Dibrov et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…1A) (6). Domain II is nearly 100% conserved in clinical isolates (7) and has analogous counterparts in other viral IRES elements, all of which display some secondary structure similarity, but significant sequence variation in the subdomain IIa-like internal loop (Fig. 1B).…”
mentioning
confidence: 97%
“…1D) that bind to the internal loop and block translation by capturing distinct conformational states of the RNA (7). Structure analysis revealed that benzimidazole inhibitors such as compound 1 (19,20) interact with an extended architecture of IIa in which the stems flanking the internal loop are coaxially stacked on both sides of the ligand-binding pocket ( Fig.…”
mentioning
confidence: 99%
“…Much effort has been dedicated to the development of drugs that could impair IRES-mediated translation as a means of blocking viral replication, mainly focusing on the HCV IRES (Dibrov et al 2012(Dibrov et al , 2014. Recently it has been proposed that cap-independent expression of vFLIP could provide a mechanism to control the balance between vCyclin and vFLIP levels, thereby allowing vFLIP to suppress autophagy and inhibit senescence during latent infection (Leidal et al 2012).…”
Section: Vflip Ires Activity Requires Eif4g and Eif4ementioning
confidence: 99%